2016
DOI: 10.5860/crl.77.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Employer Perceptions of Critical Information Literacy Skills and Digital Badges

Abstract: Digital badges are an educational innovation used to measure learning of specific skills, such as information literacy. However, few studies have quantitatively surveyed employers for their perceptions about information literacy skills or digital badges. An online survey was developed and sent to employers to gauge perceptions of information literacy skills of college graduates and the use of the innovation of digital badges to represent competencies that students have accumulated. Here are the results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 28 publications
2
25
0
2
Order By: Relevance
“…Similarly, De Saulles () attributed loss of business income in the United Kingdom to inefficient searching for information. Others have reported that many workforce employees lack the skills to use information effectively (Head, ; Raish & Rimland, ; Thompson, ).…”
mentioning
confidence: 99%
“…Similarly, De Saulles () attributed loss of business income in the United Kingdom to inefficient searching for information. Others have reported that many workforce employees lack the skills to use information effectively (Head, ; Raish & Rimland, ; Thompson, ).…”
mentioning
confidence: 99%
“…Liyanagunawardena, Scalzavara, and Williams (2017) Recently, in a study examining the opinions of education employers, it was discovered that upon learning about education badges, education employers felt that such badges could be valuable pieces in an application (Randall & West, in press). Another study (Raish & Rimland, 2016), found in a nationwide survey of employers in the United States, that only 5% would not be interested in open badges. However, the concept is still largely unknown with employers, as Raish and Rimland (2016) also found that 62% of the respondents wanted to learn more about open badges.…”
Section: )mentioning
confidence: 99%
“…Another study (Raish & Rimland, 2016), found in a nationwide survey of employers in the United States, that only 5% would not be interested in open badges. However, the concept is still largely unknown with employers, as Raish and Rimland (2016) also found that 62% of the respondents wanted to learn more about open badges.…”
Section: )mentioning
confidence: 99%
“…Meanwhile there are eight key elements that characterize digital literacy, which are mutual understanding and respect for a culture, as well as to have cognitive digitalization, and a constructive, communicative, confident, creative, critical, and civic understanding (knowing how to use technology to increase civic engagement and social action) in the digital environment with a global scope [28]. Other categories in conceptualizing digital literacy are (a) innovation, (b) thinking critically and using quality information, (c) collaboration, (d) technology, ethics, and self-awareness, and (e) finding and gathering information [29]. The understanding of digital literacy is further defined by The ALA Digital Literacy Task Force as the ability to use information and communication technology to find, evaluate, create and communicate information that requires technical and cognitive skills [30].…”
Section: B the Relationship Of Digital Literacy With Global Insightsmentioning
confidence: 99%